BAKTI SOSIAL SUNATAN MASSAL DI PERUMAHAN GRIYA BATU AJI TAHAP 1 ,2 DAN 3 RW 16 KELURAHAN SUNGAI LANGKAI KECAMATAN SAGULUNG KOTA BATAM - Winda Evyanto; Mhd. Johan (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
The cost of circumcision which is starting to become unaffordable to the public and coupled with the outbreak of the most frightening virus, namely